Defect engineering in perovskite oxide thin films. Issue 68 (5th August 2021) - Sun, Yunlong; Yang, Jack; Li, Sean; Wang, Danyang
Abstract : The modulation of properties in perovskite oxide thin films by defect engineering. Abstract : Perovskite oxide thin films are a category of multifunctional materials that have intriguing electrical, magnetic, and photovoltaic properties that can be harnessed combinatorially in future microelectronic devices. However, the inevitable existence of defects in perovskites, regardless of the materials' processing conditions, plays a significant role in their functional properties, which could be either detrimental or beneficial, depending on the exact chemical nature of these defects. As such, defect engineering is an important research area in perovskite thin films that aims at understanding the chemical nature of the defects, from which the physical properties of materials can be more precisely manipulated. Here, we review the common defects in perovskite oxide thin films, which include point defects, dopants, domains and domain walls. The factors that impact the appearance and existence of defects and the corresponding mechanisms are also discussed. While summarizing our previous work, the state-of-the-art in the field from other groups has also been discussed. Most of the defects exist as defect dipoles that affect the oxidation states of relevant ions and induce anomalous behaviors, such as ferroelectricity in otherwise non-ferroelectric thin films, as well as enhanced electrical conductivity in insulators. Furthermore, the couplings between defect dipoles and other degrees of freedom including epitaxial strains and interfaces also provide new strategies to modulate the functional properties of perovskite thin films. Particularly, the coupling between defects and domain wall motion can be regarded as a universal tool to modulate the electric and magnetic properties of thin films of perovskite oxides. It is our hope that this review could promote defect engineering as a general regulation strategy to embellish the functional properties of perovskite oxide thin films.